Rice bran extract: an inexpensive nitrogen source for the production of 2G ethanol from sugarcane bagasse hydrolysate - Milessi, Thais S. S. (Springer Berlin Heidelberg, 2012)
Selection of the raw material and its efficient utilization are the critical factors in economization of second generation (2G) ethanol production. Fermentation of the released sugars into ethanol by a suitable ethanol producing microorganism using cheap media ingredients is the cornerstone of the overall process. This study evaluated the potential of rice bran extract (RBE) as a cheap nitrogen source for the production of 2G ethanol by Scheffersomyces (Pichia) stipitis NRRL Y-7124 using sugarcane bagasse (SB) hemicellulosic hydrolysate. Dilute acid hydrolysis of SB showed 12.45 g/l of xylose and 0.67 g/l of glucose along with inhibitors. It was concentrated by vacuum evaporation and submitted to sequential detoxification (neutralization by calcium hydroxide and charcoal adsorption). The detoxified hydrolysate revealed the removal of furfural (81 %) and 5-hydroxymethylfurfural (61 %) leading to the final concentration of glucose (1.69 g/l) and xylose (33.03 g/l). S. stipitis was grown in three different fermentation media composed of detoxified hydrolysate as carbon source supplemented with varying nitrogen sources i.e. medium #1 (RBE + ammonium sulfate + calcium chloride), medium #2 (yeast extract + peptone) and medium #3 (yeast extract + peptone + malt extract). Medium #1 showed maximum ethanol production (8.6 g/l, yield 0.22 g/g) followed by medium #2 (8.1 g/l, yield 0.19 g/g) and medium #3 (7.4 g/l, yield 0.18 g/g).